Spatial Configuration Of The Lesehan Restaurant in Garut Based on Visitors' Perception - Arfiadjie Rayina; Indyah Martiningrum (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, 2023)
Restaurant as one of the commercial buildings that can meet the primary needs of society. In tourist areas, restaurants are not only a place to eat but also a place to rest and recreation. Garut as one of the districts which is a tourist destination in West Java has a fairly high development of restaurants. The restaurant that will be focused on in this research is a restaurant with a cross-legged concept which usually has a large area. So that restaurants with this concept have a variety of layouts. Visitors as parties who are the key to the success of a restaurant have their own perceptions of the restaurant, they are interested in. This study aims to determine visitor perceptions of the spatial configuration of restaurants with the Lesehan concept in Garut. The quantitative method is used through a public perception approach where respondents are asked to assess seven variables related to micro-spatial configuration (zoning, circulation, spatial pattern, arrangement and configuration of furniture, supporting facilities such as toilets; prayer rooms; and parking). The results showed a positive score for all assessments, where zoning had the highest score and toilet support facilities had the lowest score. Furthermore, the results can be used as a reference for restaurant managers in building a restaurant with a cross-legged concept.